The Structural Properties of Nano-Coppers Synthesized via the Electric Wire Explosion Method and Application as Anti- Escherichia coli Bacterial - Sawsan T. Jumaa; Baha'a A. M. Al Hilli; Ausama I. Khudiar (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
In this research, copper nano powders Cu NPs were successfully prepared via laser triggering wire explosion technique at different explosion voltage (4, 5 and 7 KV). It was observed through X-ray diffraction examinations that the prepared powders have a polycrystalline structure and their characteristic peaks correspond to copper and copper oxide. FE-scanning electron microscopy images showed that the prepared powders had a nanostructure and regular morphology, and the regularity increased with increasing explosion voltage. Antibacterial activity tests showed the efficiency of the prepared powders in eliminating Escherichia coli bacteria, especially the powder prepared at 7KV voltage and at concentration 200 µg/mL.